Early Changes of the Cortical Micro‐Channel System in the Bare Area of the Joints of Patients With Rheumatoid Arthritis. Issue 8 (26th June 2017) - Werner, David; Simon, David; Englbrecht, Matthias; Stemmler, Fabian; Simon, Christoph; Berlin, Andreas; Haschka, Judith; Renner, Nina; Buder, Thomas; Engelke, Klaus; Hueber, Axel J.; Rech, Jürgen; et al.
Abstract : Objective: To characterize the specific structural properties of the erosion‐prone bare area of the human joint, and to search for early microstructural changes in this region during rheumatoid arthritis (RA). Methods: In the initial part of the study, human cadaveric hand joints were examined for exact localization of the bare area of the metacarpal heads, followed by detection of cortical micro‐channels (CoMiCs) in this region by high‐resolution peripheral quantitative computed tomography (HR‐pQCT) and, after anatomic dissection, validation of the presence of CoMiCs by micro–computed tomography (micro‐CT). In the second part of the study, the number and distribution of CoMiCs were analyzed in 107 RA patients compared to 105 healthy individuals of similar age and sex distribution. Results: Investigation by HR‐pQCT combined with adaptive thresholding allowed the detection of CoMiCs in the bare area of human cadaveric joints. The existence of CoMiCs in the bare area was additionally validated by micro‐CT. In healthy individuals, the number of CoMiCs increased with age. RA patients showed significantly more CoMiCs compared to healthy individuals (mean ± SD 112.9 ± 54.7/joint versus 75.2 ± 41.9/joint; P  < 0.001), with 20–49‐year‐old RA patients exhibiting similar numbers of CoMiCs as observed in healthy individuals older than age 65 years. Importantly, CoMiCs were already found in RA patients very early in their disease course, with enrichment in the erosion‐prone radial side of the joint. Conclusion: CoMiCs represent a new form of structural change in the joints of patients with RA. Although the number of CoMiCs increases with age, RA patients develop CoMiCs much earlier in life, and such changes can even occur at the onset of the disease. CoMiCs therefore represent an interesting new opportunity to assess structural changes in RA.